The challenge of education for sustainability in higher education: key themes and competences within the University of the Basque Country - Idoiaga Mondragon, Nahia; Yarritu, Ion; Saez de Cámara, Estibaliz; Beloki, Nekane; Vozmediano, Laura (Frontiers in Psychology, 2023)
One of the major challenges for higher education institutions in the last decade has been (and will continue to be) the integration of sustainability into their curricula and the development of sustainability competences in students. Education for Sustainability (ES) can help prepare students to meet the challenges of making societies more sustainable. However, the first step for this will be for teachers to incorporate ES into their teaching. In this regard, this research aimed to analyze if teaching staff has started this integration and, if this is the case, what topics linked to sustainability have been introduced by faculty staff and which competences they consider contribute to the development of future graduates. A questionnaire was administered to teaching staff at the University of the Basque Country in 2022. A total of 403 teachers completed the questionnaire, expressing their perceptions through open-ended questions. The results revealed that, in general terms, teachers incorporate ES into their teaching (71.22 %). However, they do this mainly within the framework of two general topics: "Environmental awareness and energy," most used by teachers of experimental sciences and engineering, and "Social commitment," most used by teachers of social sciences and those who are familiar with the UN 2030 Agenda for Sustainable Development. Regarding the competences for sustainability that ES provides to future graduates, those most frequently mentioned were “training of professionals committed to society” and “critical thinking and ethics," particularly by teachers who were aware of the 2030 Agenda and by those who use active methodologies. Finally, one group of teachers expressed that, in their opinion, sustainability has nothing to do with their teaching (28.78%), an idea associated with those less familiar with the 2030 Agenda. These findings were discussed in relation to the previous literature on ES. Thus, it can be concluded that knowledge of the 2030 Agenda, together with factors such as the policy of the institution regarding sustainability, area of knowledge, and the use of active methodologies, all promote the integration of sustainability and its competences in higher education teaching.